(untitled) - Bryan Pfaffenberger (New York, 1991)
It provides an introduction to microcomputer application tools ( DOS, Wordperfect 5.1, Lotus 1-2-3 versions 2.0 and 2.2 and dBase iV version 1.1). It pioneers the marriage of the skill appoach and the concepts approach for the appications software class. It was written from the biginning with a single goal: to make the most of the fruitful interplay between the learning of skills and the learning of concepts. Students learn not only which key to press, but even more, how to expert computer knowledge to new applications and the new computing enviroments.
Keywords: dBase IV ( computer program ),lotus 1-2-3,microcomputers,wordperfect ( computer program )